Penggunaan Mind Mapping dengan Aplikasi Canva untuk Meningkatkan Keterampilan Mengajar Guru di SMP Maju Jaya, Surabaya - Yohanes Calvin Fallo; Soegeng Wahyudi; Januar Budiman; Edi Joko Santoso (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
Teachers have a big role in providing knowledge and instilling positive values in students so teachers must have the skills to organize inspiring, challenging, fun and innovative learning for students. However, there are still many teachers who do not have good teaching skills. This study aims to determine how the use of mind mapping with the Canva application can improve teacher teaching skills at Maju Jaya Surabaya Junior High School. The research method used was school action research consisting of two cycles. This study examined the teaching skills of two teachers, namely Civics teachers and Mathematics teachers at Maju Jaya Surabaya Junior High School. Data collection techniques used observation, questionnaires and interviews. The success indicator of this study is the percentage of teachers' teaching skills reaching 75%. The results of this study show that in the first cycle, the percentage of teaching skills of Civics teachers increased to 62.5% while the percentage of teaching skills of Mathematics teachers increased to 71.8%. After making improvements in the second cycle, the percentage of Civics teachers' teaching skills increased again to 78.12% while the percentage of Mathematics teachers' teaching skills increased to 93.75%. This result also shows that the application of mind mapping with Canva application can improve teacher skills and also the use of this method has a more significant effect on Mathematics teachers.